CD34+ UCB stem cells attenuate TGF-β signaling and inhibit liver fibrosis: A new avenue for liver cirrhosis-carcinogenesis prevention - Septiana, Wahyunia Likhayati; Antarianto, Radiana Dhewayani; Louisa, Melva; Jusuf, Ahmad Aulia; Barasila, Atikah Chalida; Pawitan, Jeanne Adiwinata; Fasha, Iqbal (UI Scholars Hub, 2020)
Background: The liver microenvironment plays a key role in liver fibrosis and carcinogenesis. This study aimed to fill the gap in knowledge on the interaction between hepatic stellate cells and endothelial progenitor cells with biomarkers of liver fibrosis and/or carcinogenesis, including Col1A1, TGF-β, and tenascin-C. Methods: CD34+ stem cells were isolated from umbilical-cord-blood mononuclear cells. 2D and 3D co-culture of CD34+ UCB SCs and LX2 was performed. The cells were incubated in a CO2 incubator for three days. Morphological observation, qRT-PCR of TGF-β1 and COL1A1, and immunocytochemistry of tenascin-C were performed. Results: CD34+ UCB SCs were viable in the 2D and 3D co-culture for 24 h. 3D co-culture of CD34+ UCB SCs and LX2 inhibited in vitro liver fibrosis by lowering Col 1A1 expression as compared to control. We observed lower TGF-β expression in 3D co-culture on days 1 and 2 followed by higher expression of TGF-β on day 3. 2D co-culture of CD34+ UCB SCs and LX2 showed a different level of COL1A1 and TGF- β expression compared with 3D co-culture. Spheroids from 2D co-culture of CD34+ UCB SCs and LX-2 showed immunoreactivity against tenascin-C. Conclusion: Interaction between LX-2 and CD34+ UCB SCs in 3D co-culture inhibits in vitro liver fibrosis. The viability of CD34+ UCB SCs is essential for attenuation of TGF-β signaling in LX-2.